THE CHAK DYNASTY IN JAMMU AND KASHMIR: A FORGOTTEN LEGACY - Shabir Ahmad Lone; R Abida Begum (PT. Radja Intercontinental Publishing, 2025)
Marcus Garvey, a proponent of Black Nationalism in the United States, likened a people without historical awareness to a tree without roots. Inspired by this perspective, I explored the historical canon of Kashmir, Jammu, and other Chak Dynasty territories. As residents of Jammu and Kashmir, understanding regional history is crucial. This study examines the Chak Dynasty’s legacy, highlighting its governance from 1561 to 1586. Although administrative records are scarce, the Chaks maintained and reinforced existing institutions. The research investigates their rule, emphasizing their influence on Kashmir’s political and economic structures and its transition under Muslim dominion.